Analysis of the competitive performance of school category volleyball players in Havana/Análisis del rendimiento competitivo de las jugadoras de voleibol categoría escolar de La Habana - Alfonso Pau de la O; Pedro Manuel Téllez Quezada; María Luisa Cáceres Ponce (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2021)
The demands of high performance sport and the changes that have been taking place in it, demand adequate preparation of future female volleyball players of school categories. In a documentary search it was possible to verify the non-existence of parameters and real values at national level on the physical, technical and tactical behavior of volleyball teams of school categories in Cuba. Based on this, the objective of the present work is focused on analyzing the competitive performance of 13-15-year-old female volleyball players in Havana, where certain indicators were used to evaluate the behavior of the players during the competition, among them: percentage of points obtained by own actions or errors of the opponent, as well as the number of jumps per game, set and match functions. Scientific methods were used such as direct observation to evaluate the desired elements; surveys to coaches; review of documents and mathematical methods to tabulate the information that generates important demands for the adjustment in the training loads that will be applied to the athletes in the next season. The control of these parameters is of importance in the planning of the preparation of the athletes, allowing the coaches to develop in an effective way the process of training management in these categories.